Domestic and Foreign Firms in Russian Food Industry for the Period of 2005-2014 - Spitsin, Vladislav; Mikhalchuk, Alexandr; Novoseltseva, Darya; Boznyakov, Anton; Spitsina, Lubov; Antonova, Irina (International Journal of Economics and Financial Issues, 2016)
The article studies the economic and social results of companies in Russian (domestic) ownership (RO) and companies in foreign and joint ownership (FJO) in the food industry of Russia. Using economic analysis and analysis of variance we investigated main indicators for 2005-2014 at the level of Russia and Russian regions. The analysis showed that RO firms are dominating in Russian food industry, but in some regions the foreign and joint firms are prevail. We found that the advanced development of foreign firms was observed during the period of 2005-2013, but the joint firms’ share decreased for this period. In 2014 the significant growth of RO firms’ production volumes was revealed. RO firms in 2005-2014 were characterized by employment decrease and labor intensity fall. The FJO firms’ employment was stable but they have significantly less employment and much less labor intensity (lower social results) in a comparison with RO firms. Keywords: Domestic and foreign and joint enterprises, food industry, economic analysis, analysis of variance, Russia and Russian regions. JEL Classifications: O100, L660, C100.